Mine closure planning and social responsibility in Western Australia – recent policy innovations - Morrison- Saunders, A.; Pope, Jennifer (SMICSRM, 2013)
Social responsibility should be embedded into all phases of the mining project cycle. This paper presents an account of recent policy and legislation for mine closure planning in Western Australia focusing on how social responsibility is accommodated. Policy and legal provisions are reviewed along with secondary accounts from government sources. Mine closure in Western Australia is regulated in two main ways: mine closure planning and mining proponent contributions to a mining rehabilitation fund. Mine closure plans must be prepared within mining and/or environmental assessments. Proponents must regularly review them for the duration of mining with increasing level of detail as the life of mine advances. Financial provisioning for mine closure is also included. Key stakeholders must be consulted by mining proponents to determine post mining land uses and these are incorporated into mine closure plans before new mining projects will be approved. In addition to biophysical specifications in mining authorisations, the stakeholder consultation process likely will give rise to social responsibility measures in mine closure plans. Under the new mining rehabilitation legislation which was developed in consultation with mining industry stakeholders, proponents will be levied annually at one per cent of the rehabilitation liability estimate per mining tenement.The money collected goes into a central fund. Interest earned will be used to rehabilitate legacy abandoned mines while the capital will be used to rehabilitate any abandoned mine sites covered by the fund. The fund overcomes limitations of the former individual performance bonds system. Rehabilitation must be in accordance with mining authorisations which will invoke the mine closure plan framework and its implicit social responsibility provisions. The new Western Australian mine closure policy and regulatory framework offers a means for effectively managing both planned and unintended mine closure including implicit consideration of social responsibilities by mining proponents and government alike.